The risk management role of nonexecutive directors: from capital expenditure perspective - Tho Anh To; Yoshihisa Suzuki; Hong Thu Thi Ho; Siem Thi Tran; Tuan Quoc Tran (European Journal of Management and Business Economics, 2021)
Purpose – This study investigates the impact of board independence on firm risk of Vietnamese listed firms and the moderating effect of capital expenditure on this relationship. Design/methodology/approach – This paper applies fixed effects and dynamic generalized method of moments (GMM) models to examine hypothesized associations between the proportion of nonexecutive directors and stock return volatility, as well as the moderating effect of capital expenditure. The robustness tests are implemented by applying alternative measures of overinvestment and firm risk. Findings – The results show that the presence of nonexecutive directors on board increases firm risk. However, the combination of nonexecutive ratio and capital expenditure ratio has a significant negative impact on firm risk. The result is also confirmed by the difference between the monitoring role of nonexecutive directors in overinvesting and underinvesting firms. Research limitations/implications – The results imply that Vietnamese listed firms take stock return volatility into consideration before nominating and appointing nonexecutive directors into their board, especially in overinvesting firms. From another perspective, the shift toward having a majority of nonexecutive directors on boards can play a significant role in pursuing a stable or risky business strategy. Originality/value – This paper investigates the influences of nonexecutive directors on firm risk in the context of Vietnam.